تخفيض عتبة جهد المفاعيل الكهرضوئية في البلورات السائلة بالتحكم بالظروف السطحية للخلية الكهرضوئية - غزولين عصام محمد (Latakia University Journal -Engineering Sciences Series, 2019)
استخدمت البلورات السائلة بنجاح منذ بدايات عام 1970 في إظهار المعلومات الرقمية على شاشات الآلات الحاسبة و شاشات التلفزة (الأنابيب المهبطية ) . إحدى أهم الإشكالات في استخدامها، يكمن في أن عتبة جهد المفاعيل الكهرضوئية فيها عالية نسبيا" ولا تزال الأبحاث مستمرة في جعل هذا الجهد أكثر ملاءمة"، تقليلا" للكلفة و تسهيلا" للحصول على مساحات كبيرة لصنع شاشات إظهار مسطحة تحل محل الشاشات العادية المستخدمة الآن. يهدف بحثنا هذا إلى إيجاد طرق تخفيض عتبات جهد المفاعيل الكهرضوئية للنماذج الصابونية (SA) و (SC) و ذاتية الاستقطاب. قمنا بدراسة عدد من المركبات خلال النصف الأول من عام 2001 ووجدنا بأن استخدامها يصبح أكثر قدرة على المنافسة إذا توصلنا إلى تخفيض الجهد المطبق على الخلايا البلورية السائلة. The liquid Crystals have been used successfully since 1970 as a display in digital calculators and TV screen (cathode tubes). One of the important problems in their use, resides in the fact that its threshold voltags of the electro – optic effect are relatively high. Reseachers are still trying to make these voltags more convenient, in order to decrease the cost and facilitate obtaining large surface displays to replace cathode tubes in use. This article aims to find ways of cutting down the threshold voltage of different kinds of liquid crystal, Smectic (SA) , (SC) and ferroelectrics. In the first half of the year 2001, we’ve studied many components and found that its use becomes more competitive if the voltage applied on the liquid crystal cells can be reduced.